1988
DOI: 10.1079/bjn19880055
|View full text |Cite
|
Sign up to set email alerts
|

The action of the β-agonist clenbuterol on protein and energy metabolism in fattening wether lambs

Abstract: 1. Five Greyface wethers (4245 kg) fed on various fixed amounts of dried grass pellets (either approximately 1.3 times maintenance or 2 times maintenance) by means of belt-type continuous feeders were housed in opencircuit respiration chambers for periods of 45 d. Between days 15 and 35 they received daily oral doses of 1.5 mg of the p-adrenergic agonist clenbuterol (adsorbed on to the feed). Continuous energy and nitrogen balance measurements each of 5 d duration were conducted throughout the chamber confinem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
1

Year Published

1990
1990
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(24 citation statements)
references
References 14 publications
1
22
1
Order By: Relevance
“…This result was unexpected and discordant with most previous studies in which nitrogen retention was increased for BAA-treated animals (MacRae et al 1988;Kim et al 1989;Wenk et al 1989). However, carcass analysis in the present study showed that accretion in muscle tissues was enhanced in BAA-treated animals, as indicated by increased ribeye area and biceps femoris weight.…”
Section: Nitrogen Retentioncontrasting
confidence: 50%
See 1 more Smart Citation
“…This result was unexpected and discordant with most previous studies in which nitrogen retention was increased for BAA-treated animals (MacRae et al 1988;Kim et al 1989;Wenk et al 1989). However, carcass analysis in the present study showed that accretion in muscle tissues was enhanced in BAA-treated animals, as indicated by increased ribeye area and biceps femoris weight.…”
Section: Nitrogen Retentioncontrasting
confidence: 50%
“…Under normal conditions, heart rate is closely related to metabolic rate (Yamamoto 1989). Higher heart rate may indicate a higher metabolic heat production, as other researchers have reported that BAA increased fasting heat production and maintenance requirements for energy (Kim et al 1989) and total energy expenditure (MacRae et al 1988).…”
Section: Carcass Traitsmentioning
confidence: 90%
“…β-adrenoceptor processes mediate protein accretion in animals (Choo et al 1992). Simulation by β-adrenergic agonists results in increased thermogenesis and protein accretion in ruminants (MacRae et al 1988). The blockade of β-adrenergic receptors may reduce metabolic rate and, therefore, maintenance energy requirements, which would be beneficial for energetic efficiency.…”
mentioning
confidence: 99%
“…Obviously, other mechanisms adversely affect feed conversion. A higher energy requirement for maintenance due to an increased heat production has been reported for (3-agonist-treated rats (Sainz and Wolff, 1988), lambs (MacRae et al, 1988) and calves (Williams et al, 1987). If this mechanism affects the efficiency of energy utilization, then there is no reason to suppose that it is more important towards the end of the experiment, on the contrary.…”
Section: Fortymentioning
confidence: 87%
“…The higher protein deposition in cimaterol-treated bulls and the accompanying deposition of water (van Es, 1977;Robelin and Geay, 1978) suggest a lower energy requirement per unit of tissue. Furthermore, the decreased protein turnover in cimateroltreated animals (Williams et al, 1987;MacRae et al, 1988;Fiems et al, 1990) is another argument for an improved feed conversion. Obviously, other mechanisms adversely affect feed conversion.…”
Section: Fortymentioning
confidence: 99%